1983
DOI: 10.1042/bj2090387
|View full text |Cite
|
Sign up to set email alerts
|

Structure of proteoglycans from different layers of human articular cartilage

Abstract: Full-depth plugs of adult human articular cartilage were cut into serial slices from the articular surface and analysed for their glycosaminoglycan content. The amount of chondroitin sulphate was highest in the mid-zone, whereas keratan sulphate increased progressively through the depth. Proteoglycans were isolated from each layer by extraction with 4M-guanidinium chloride followed by centrifugation in 0.4M-guanidinium chloride/CsCl at a starting density of 1.5 g/ml. The efficiency with which proteoglycans wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
3
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(141 citation statements)
references
References 37 publications
10
127
3
1
Order By: Relevance
“…Under the experimental conditions used in our studies, extraction with 4.OM GuHCl was not quantitative, since some 30% of the total PGs in both loaded and unloaded cartilage remained in the tissue after extraction with this solvent. However, Bayliss et a1 (33) have shown that the yield of PGs extracted with 4.OM GuHCl is related to the amount of surface area of cartilage available to the solvent. Thus, in their studies, virtually all the PGs were extracted from articular cartilage when the tissue had been sectioned on a microtome into slices only 20p thick.…”
Section: Discussionmentioning
confidence: 99%
“…Under the experimental conditions used in our studies, extraction with 4.OM GuHCl was not quantitative, since some 30% of the total PGs in both loaded and unloaded cartilage remained in the tissue after extraction with this solvent. However, Bayliss et a1 (33) have shown that the yield of PGs extracted with 4.OM GuHCl is related to the amount of surface area of cartilage available to the solvent. Thus, in their studies, virtually all the PGs were extracted from articular cartilage when the tissue had been sectioned on a microtome into slices only 20p thick.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated the presence of regional differences in articular chondrocyte responses to mechanical loading, suggesting the possibility that even under uniform loads different cartilage regions may not respond uniformly (Bevill et al, 2009). As chondrocytes are particularly sensitive to the three-dimensional microenvironment and differentiate in response to local signals (Lemare et al, 1998;Goldring, 2004a;Goldring, 2004b), the expression of cartilage ECM elements likely exhibit regional variation due to subtle differences in loading patterns in distinct joint regions (Bayliss et al, 1983;Nakano and Scott, 1989;Mow et al, 1990;Mizoguchi et al, 1996;Tanaka et al, 2000). It is unknown how velocity-related changes in limb posture affect load orientation.…”
Section: P<005 Limb Loading and Joint Plasticitymentioning
confidence: 99%
“…More recent work provides considerable support for the hypothesis that cartilage of the mandibular condyle and TMJ articular disc is affected by local biomechanical effects. Indeed, chondrocytes are highly sensitive to 3-D microenvironment and exhibit changes in differentiation status in response to environmental cues (Lemare et al, 1988;Goldring, 2004a;Goldring, 2004b), with expression of cartilage ECM elements likely reflecting regional variation due to differential loading patterns in distinct joint regions (Bayliss et al, 1983;Nakano and Scott, 1989;Mow et al, 1990;Hamrick, 1999;Tanaka et al, 2000). In this regard, it is interesting that collagen-and proteoglycan-degrading proteinases have been reported in TMJ tissues and synovial fluids (Kiyoshima et al, 1993;Kiyoshima et al, 1994;Marchetti et al, 1999;Puzas et al, 2001;Srinivas et al, 2001).…”
Section: Adaptive Plasticity and Degradation In Masticatory Tissuesmentioning
confidence: 99%